Molecular characterization of buffalo αs1-casein gene - Pramanik, Biplab Kumar; Batabyal, Subhasis; Maity, Apratim; De, Sachinandan; Chattopadhyay, Saibal; Barui, Abhijit (Buffalo Bulletin, 2022)
The caseins (Alpha s1, Alpha s2, beta and kappa) comprise the major protein component of ruminant milk and are secreted in the form of stable calcium phosphate micelles. The present study was proposed to characterize αs1-casein gene in buffalo at the molecular level to determine complete αs1-casein cDNA sequence. Sequencing results were analyzed and aligned with available mRNA GenBank sequences of other domestic animals (Accession AAB34797, NM_001009795, X72221, AY344966, NM_181029, AY948385 and BC109618). The complete amino acid coding region of the buffalo αs1- casein was deduced from cloned cDNA generated from mammary tissue mRNA. Amino acid sequence comprises of 199 amino acid residues. When aligned with previously reported buffalo sequence (Accession-AY948385) it showed one amino acid (Glutamine) deletion at amino acid position 78.